Synthesis, electrochemical and spectroelectrochemical characterization of novel soluble phthalocyanines bearing chloro and quaternizable bulky substituents on peripheral positions - KOCA, ATIF (ELSEVIER SCI LTD, 2012)
A new phthalonitrile derivative (2), bearing diethylaminophenoxy - and chloro-substituents at peripheral positions was synthesized in this work. Cyclotetramerization of (2) in hexanol gave the desired metal-free (4) and metallophthalocyanines (5-8). These new phthalocyanines (4-8) were converted into water-soluble quaternized products by the reaction with methyl iodide (9-11). The novel compounds have been characterized by using elemental analysis, UV-Vis, FT-IR, H-1 NMR and MS spectroscopic data. The aggregation behaviors of the phthalocyanine complexes wet e studied in different solvents and concentrations. Electrochemical and spectroelectrochemical characterization of the complexes were also performed in solution. Cobalt phthalocyanine gives both metal-based and ring-based reduction processes in comparison to the complexes having 2H(+), Zn2+, Ni2+ and Cu2+ metal center which give only ring-based reduction processes. Electrochemical and spectroelectrochemical measurements exhibit that all complexes oxidatively electro-polymerize on the Pt working electrode during repetitive cyclic voltammetry measurements. An in-situ electrocolorimetric method was applied to investigate the color of the electrogenerated anionic and cationic forms of the complexes for possible electrochromatic applications. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Diethylaminophenoxy; Water-soluble; Aggregation behavior; Electrochemistry; Spectroelectrochemistry; METAL-FREE; IN-SITU; PHOTODYNAMIC THERAPY; METALLOPHTHALOCYANINES; COBALT; TERTIARY; CO(II); COPPER